The Nigeria Police Philosophy and Administration of Criminal Justice Post 2015: Interrogating the Dissonance - Akinsulore, Adedoyin Olusegun (Sriwijaya Law Review, 2020)
The importance of the enactment of the Administration of Criminal Justice Act (ACJA) 2015 for the Nigerian Federation and the subsequent state variants have an impact on the need for speedy dispensation of justice. This enactment enjoins all institutional actors that make up the criminal justice system in Nigeria to accelerate the processes leading to the quick dispensation of justice for the defendant, the victim and the society. The Nigeria policing philosophy characterised by centralised command and control governance system appears to be at variance with this aim as provided by the Act. It is particularly so in component states where variants of the ACJA have not been enacted. Quick dispensation of justice may be painful to achieve when the police cannot be controlled by any other body in the Federation other than the central command. This paper provides that if there is no realignment or a total recalibration of the philosophies between the ACJA and the Nigeria Police, the aims of ACJA may become far from reality. The combination of jurisdictional limitation of crime and the peculiar federating structure of the country which imposes a pseudo-independent criminal justice system on each state has a crucial impact on the aims of ACJA.